Utilization of Okra (Abelmoschus esculentus L. Moench.) - Hodossi, Sándor; Csontos, Györgyi (Acta Agraria Debreceniensis, 2002)
Okra is warm season crop native to Africa. Presently it is widely grown in the northeastern parts of Brazilia, both northen, and western parts of Africa, southeast Asia, and in the eastern parts of the Mediterraneum. In Hungary it is a rarity. It’s adaptation to Hungary began about 40 years ago.The optimal sowing time under Hungarian climatic conditions is middle of May. The harvests is started – depending on the weather – first, by the middle of July, and picking continues until the first of September. According to our results, seed soaking, sowing under a perforated foil sheet-covered trench (2 weeks earlier the normal sowing time), and 55-65 g thousand weight seeds are favourable. The harvest period under Hungarian circumstances is appr. one and half months.